IMPLEMENTASI SCL UNTUK MENAMBAH KOMPETENSI SISWA SMK DALAM MEMONITOR PROYEK IOT MELALUI PLATFORM BLYNK: SCL IMPLEMENTATION TO ADD VOCATIONAL SCHOOL STUDENT COMPETENCE IN MONITORING IOT PROJECTS THROUGH THE BLYNK PLATFORM - Yoanda Alim Syahbana; Sugeng Purwantoro E.S.G.S; Memen Akbar; Wenda Novayani; Mardhiah Fadhli (LPPM Universitas Abdurrab, 2023)
SMK Taruna Persada Dumai is one of the vocational schools that participate in the SMK Center of Excellence program. This program focuses on developing specific skill competencies for SMK students. Competency development is prioritized on competencies that are aligned with the business world, industrial world, and world of work. Based on the evaluation of the previous year's Community service activities, the SMK Taruna Persada Dumai asked to continue the activity to increase its students’ competencies. The competency that will be taught in the 2022 Community service PSTRK is an introduction to the field of IoT which is currently developing. PSTRK implements Student-Centered Learning (SCL) to increase the competency of SMK students in monitoring IoT projects through the Blynk platform. Community service was held on September 6, 2022, from 9.00 am to 14.00 pm. This activity was attended by 20 students from the Department of Computer Network Engineering, SMKS Taruna Persada Dumai City. The given SCL module consists of 5 parts. The first part focuses on the small group discussion learning model in the introduction of processors, actuators, and sensors. Then, in the second part, the students simulated the LED and ESP32 circuits using the wokwi.com simulator. The third part is followed by a case study model of the LED series and NodeMCU 8266. Students’ enthusiasm for independent learning makes this third part take a long time. So, the fourth part in the form of colorful light control role-plays in the form of LED control via Blynk, and the fifth part in the form of a discovery learning model for reading DHT11 sensor data did not have time to work on it. As a solution, the Community service team left two sets of learning modules for students to work on independently later. At the end of the lesson, feedback from students was collected and the results showed their satisfaction with the material provided, the way it was presented, the quality of the modules, and the suitability of the material. The students also hope to be included in other Community service programs with different materials.